Situation analysis of rehabilitation service to support the national disability and rehabilitation plan in the Democratic People´s Republic of Korea - Boya Nugraha; Christoph Gutenbrunner (Medical Journals Sweden, 2018)
Objective: In 2013, the Democratic People's Republic of Korea (DPRK) signed the United Nations Convention on the Rights of Persons with Disabilities (UN-CRPD). Since the concept of rehabilitation services in the DPRK did not meet international standards, the government, through the Korean Federation for Protection of the Disabled (KFPD) and Munsu Rehabilitation Hospital (MRH), set up a technical consultation with external experts. Methods: Two rounds of consultations were performed, in August 2016 and March 2017, with available methodology, as used in previous consultation processes, but excluding site visits. The consultations started by collecting available data and holding workshops with representatives from the KFPD and the MRH. The results are listed as recommendations for the improvement of health-related rehabilitation services in the DPRK. The results were further developed by KFPD into a draft National Strategy and Action Plan on Comprehensive Rehabilitation (NSAPCR) 2017-2020. The draft was discussed with external experts for further improvement prior to discussion with the government. Results and discussion: Overall, the consultation processes was successful, despite the limitation of not making site visits. Recent developments in the DPRK include ratification of the UN-CRPD in December 2016. The authors hope that the NSAPCR can be implemented successfully, leading to improved quality of life for people with disabilities in the DPRK.